Respuesta :

Hey There!!

Simplify the following:

2 (-20)+3 (5/4 (-20))+5×2/5×50+4×50

5/4 (-20) = (5 (-20))/4:

2 (-20)+3×(5 (-20))/4+5×2/5×50+4×50

2/5×50 = (2×50)/5:

2 (-20)+3×(5 (-20))/4+5×(2×50)/5+4×50

3×(5 (-20))/4 = (5 (-20) 3)/4:

2 (-20)+(5 (-20) 3)/4+5×(2×50)/5+4×50

5×(2×50)/5 = (2×50×5)/5:

2 (-20)+(5 (-20) 3)/4+(2×50×5)/5+4×50

(-20)/4 = (4 (-5))/4 = -5:

2 (-20)+5×-5×3+(2×50×5)/5+4×50

(2×50×5)/5 = 5/5×2×50 = 2×50:

2 (-20)+5 (-5) 3+2×50+4×50

2 (-20)  =  -40:

-40+5 (-5) 3+2×50+4×50

5 (-5)  =  -25:

-40+-25×3+2×50+4×50

-25×3  =  -75:

-40+-75+2×50+4×50

2×50  =  100:

-40-75+100+4×50

4×50  =  200:

-40-75+100+200

-40-75+100+200 = (100+200)-(40+75):

(100+200)-(40+75)

300-(40+75)

300-115

Answer: |  185

Hope It Helps!

[tex]ItsNobody^{[/tex][tex]ItsNobody[/tex]

I did the math its 185 lol
ACCESS MORE